Exploring Education Futures: Insights from Cooperative Teachers on Elementary School Supervision - Elihami Elihami; Sitonda Syawal; Sudirman M. Yunus (E3S Web of Conferences)
This study examines the perspectives of 90 cooperative teachers engaged in early childhood teacher education practicums in Indonesia. Through questionnaires and group discussions with 14 of these teachers, the research delves into the generational backgrounds and professional training of cooperative instructors, emphasizing their diverse supervisory approaches. These approaches, categorized into six distinct types, reveal a range of perspectives: while many cooperative instructors express concerns about current teacher education programs, they also show a strong commitment to fostering the professional development of student teachers. The findings underscore a growing emphasis on “freedom and dignity of the child” within educational practices, suggesting a need for public higher education institutions to adopt more innovative approaches. This study offers valuable insights for creating a modern, crisis-resilient educational environment. Further research is essential to establish comprehensive theoretical frameworks on how practicums and supervision are shaped by complex interactions between individuals and teacher education systems, particularly given the limited attention to program variance and sociocultural contexts in teacher education.